[Nicolaus Copernicus in the Curriculum and Selected Method Books for Religion - Bielinowicz, Adam Przemysław (Studia Warmińskie, 2023)
The analysis of school curricula and religious textbooks is one of the many research tasks of catechetics, since the faith and worldview of the catechized are formed based on the content of these studies. In view of the fact that Nicolaus Copernicus is a figure of great importance both regionally, nationally and globally, he was included in the content that is conveyed to students during religion lessons. The purpose of the article is not only to present the results of the analysis of the current Roman Catholic Religious Education Program in kindergartens and schools and three method books, but also to present conclusions and postulates regarding Copernican content. In addition, an attempt has been made to answer the question to what extent a religion lesson is able to help catechized learn about the figure and views of the eminent Astronomer.